Serai Wangi Sebagai Alternatif Obat Nyamuk Alami : Potensi dan Penerapan dalam Kewirausahaan - Clara Dwi Jayantika; Mutia Ariska; Merita Auli (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Dengue fever, malaria, and other mosquito-borne diseases remain significant health problems and challenges in various regions, especially in rural areas. Dengue fever (DBD) is caused by the dengue virus types 1-4, which are transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. The majority of the residents of Karya Mukti Village work as rubber tappers. They usually start their activities early in the morning or even before dawn. However, mosquitoes are most active in the morning and late afternoon, making the local community highly vulnerable to mosquito bites. To address this issue, the people of Karya Mukti Village still widely use mosquito repellents available on the market, which contain harmful chemicals that pose risks to both health and the environment if used over the long term. Therefore, this community service initiative aims to conduct outreach and hands-on training on the use of citronella (Cymbopogon nardus) as a natural mosquito repellent alternative. This program is carried out using a socialization and product-making approach through participatory engagement, where Dasawisma (women's community groups) are encouraged to identify their needs and challenges, as well as appropriate solutions to address them. By involving Dasawisma members in the learning and production process of natural mosquito repellents, it is hoped that they will gain better knowledge and skills in making natural mosquito repellents.